The Manifestation of Inanna-Ishtar Mesopotamian Goddess in Paulo Coelho's Novel the Spy - Muhsin, Muhammad; Jaffal, Asma (Al-Adab Journal, 2025)
Mesopotamian myths occupy crucial role in literature. It's not less than Greek or Roman myths. This study concentrates on the famous Mesopotamian Goddess Inanna- Ishtar in the work of Brazilian novelist Paulo Coelho's The Spy. This Goddess is seen from very different perspectives; politics, love, fertility, wildness, and as female character articulates the ideology of feminism. The goal is to actively participate in the discourse that govern, describe, and define life. The role of women, which makes up reality, has the power to both influence and recreate the world. It reinforces the argument that there is a feminine dimension, which is seen as a force against patriarchy. The common denominator between Ishtar and Mata Hari -the heroine of this novel- is that both of them, to some extents have equivalent life. Both of them being insulted and idolized. The vulgar, wild and political role both played is the corner stone of this research. The research also illustrates both artistical and political utilization of those two characters. The research begins with an introductory section to "feminism" then using analytic argumentation to clarify Ishtar's presence in the novel The Spy. The research is then concluded based on the study's findings. Additionally, the text makes an effort to critically show how a male-female ties is really used in the context of The Spy. The study assumes that the character Mata Hari is clearly reflected in the Mesopotamian Myth Ishtar.